Modification of coconut coir as adsorbent in oil spill removal - Mohamad Mukhair, Hayati (2016)
Water pollution resulting from oil spill on water surface tends to have adverse effects on the environment and living organisms. Thus, researchers give a great deal of attention in rapid oil removal by using various types of adsorbent materials. Coconut coir, an agricultural waste, was chemically modified using esterification reaction by fatty acid chloride (oleoyl chloride and octanoyl chloride) and by graft copolymerization by using polymethyl acrylate (PMA) for oil adsorption purposes. The use of 10% (v/v) concentration of oleoyl chloride and octanoyl chloride were conclude to partial hydrophobically modified the coir surface via refluxing in DMAc/LiCl solvent system with present of 1% of NBS catalyst for 4 h at temperature range 70 - 90˚C. Besides, the PMA-g-coir was successfully prepared via refluxing of coir with 0.09 mol of methyl acrylate monomer for 2 h and at 70˚C. The maximum percentage of grafting (Pg) obtained is 136.32% respectively. The modified coir obtained was also characterized by FTIR, CHNSO analysis, FESEM, TGA, and contact angle measurement. From studies, it can be conclude oleoyl chloride is suitable fatty acid type compared to oleic acid. Besides, DMAc/LiCl is the suitable solvent system used in this study. The FTIR spectra showed that the coir was successfully esterified according to the existence of new peak corresponding to C=O carbonyl group of ester bond for long chain acyl group. Besides, the narrower peak of O-H corresponding to hydroxyl group also showed some of hydroxyl group in coir was modified. The high intensity of C-H stretching for CH2 and CH3 also indicates an increasing of alkyl group in esterified coir. For PMA-g-coir, the presence of C=O stretching of an ester functional group of polymethyl acrylate (PMA) give evidence of grafting. A new peak was also found which indicate C-H stretching in the PMA molecule. From CHNSO elemental analysis, it can be seen clearly that the percentage of C, H and O increasing upon the modification. This is due to the addition of long chain acyl group for coir-oleoate and coir-octanoate, and also due to polymethyl acrylate bond in PMA-g-coir. Thermal studied give the results that esterified coir had low thermal stability compared to raw coir due to the substitution of some hydroxyl group with acyl group which breaks the hydrogen bond in the polymer backbone. However, PMA-g-coir showed higher thermal stability compared to raw coir which indicated that grafting process improved the thermal stability of coir. The ability of coir-oleoate, coir-octanoate and PMA-g-coir to adsorb oil on the surface of water was investigated. Although PMA-g-coir showed good hydrophobic character in instrumental analysis, it showed very poor oil adsorption capacity in all parameter studied. In effect of adsorbent dosage studied, it can be seen that 0.6 g coir-oleoate was able to remove 100% of 10 mL oil with adsorption capacity 12.27 g/g compared to 10 g/g for both raw coir and coir-octanoate, while only 5.5 g/g for PMA-g-coir respectively at the same amount of adsorbent. The adsorption capacity of raw coir, coir-oleoate and coir-octanoate increase as the oil concentration increased until achieved equilibrium. In contact time study, the adsorption process seemed to occur rapidly during first 2 minutes and start to constant which showed the adsorbents displayed a fast adsorption property towards oil. The isotherm study indicated that the oil adsorption fitted well to Langmuir model rather than Freundlich model. Kinetic study showed that the oil adsorption data of raw coir, coir-oleoate, coir-octanoate, and PMA-g-coir fit well with pseudo-second-order kinetic model with correlation coefficient R2>0.99 and the experimental adsorption capacities is close to the calculated one. Water adsorption study conducted showed that modified coir adsorb water less than the raw coir both in water only and also in water-oil mixture. It showed that the new functional group present give hydrophobic properties to the coir. PMA-g-coir undoubtedly showed high hydrophobic property since it only adsorbs 20% of water in water and water-oil sample. In water-oil sample, all the adsorbents showed decreasing in water adsorption compared to in water sample. The study therefore suggests that esterified coconut coir can serve as a potential biomaterial for the adsorption of spilled oil during operational failures.